Innovation of the Internship Program and Its Implications for the Soft Skill Development of Prospective Islamic Religious Education Teachers at Sunan Kalijaga State Islamic University, Yogyakarta - Sukiman; RR. Umi Baroroh; Aninditya Sri Nugraheni; Abdulrahman Sama-alee (Jurnal Pendidikan Agama Islam)
Purpose – The objectives of this study are (1) to analyze the innovation in the implementation of internship activities at FITK and (2) to analyze the impact of internships on the soft skill development of prospective PAI teachers.